How Human Rights Can Build Haiti Activists, Lawyers, and the Grassroots Campaign - Quigley, Fran (Vanderbilt University Press, 2014)
A cataclysmic earthquake, revolution, corruption, and neglect have all conspired to strangle the growth of a legitimate legal system in Haiti. But as How Human Rights Can Build Haiti demonstrates, the story of lawyer-activists on the ground should give us all hope. They organize demonstrations at the street level, argue court cases at the international level, and conduct social media and lobbying campaigns across the globe. They are making historic claims and achieving real success as they tackle Haiti's cholera epidemic, post-earthquake housing and rape crises, and the Jean-Claude Duvalier prosecution, among other human rights emergencies in Haiti. The only way to transform Haiti's dismal human rights legacy is through a bottom-up social movement, supported by local and international challenges to the status quo. That recipe for reform mirrors the strategy followed by Mario Joseph, Brian Concannon, and their clients and colleagues profiled in this book. Together, Joseph, Concannon, and their allies represent Haiti's best hope to escape the cycle of disaster, corruption, and violence that has characterized the country's two-hundred-year history. At the same time, their efforts are creating a template for a new and more effective human rights-focused strategy to turn around failed states and end global poverty.